Breaking the cycle of shame and violence: from the individual to the global - Gerodimos, Roman (Interdisciplinary applications of shame/violence theory, 2022)
In this chapter, I identify and connect the main themes and findings emerging from the theoretical, practical and empirical analyses included in this volume, so as to shed light on the properties of the shame/violence dynamic and the ways in which this vicious cycle can be further researched and disrupted. I first examine the mechanics of the shame/violence cycle identifying four key drivers. I then identify shame in the mind, the body, language, public space and the civic culture, moving from the micro level of the individual to the macro level of communities and societies in order to examine the interaction between shame and culture. This analysis identifies shame as a mechanism of social organisation in anarchic environments of unaccountable power. Therefore, it is argued that a power-literate approach to shame and violence is required in order to address it. I then consider the challenges facing practical interventions in the community in light of this volume’s contributions. The chapter concludes with a series of recommendations, interventions and principles emerging from this volume that have the potential to disrupt this cycle.